2019
DOI: 10.1681/asn.2019070651
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pig Kidney Xenotransplantation: How Close Are We?

Abstract: Patients with ESKD who would benefit from a kidney transplant face a critical and continuing shortage of kidneys from deceased human donors. As a result, such patients wait a median of 3.9 years to receive a donor kidney, by which time approximately 35% of transplant candidates have died while waiting or have been removed from the waiting list. Those of blood group B or O may experience a significantly longer waiting period. This problem could be resolved if kidneys from genetically engineered pigs offered an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 68 publications
0
46
0
1
Order By: Relevance
“…Selecting baboons that have a low or negative CDC to pig cells will be important in mimicking the pig-to-human model (as many humans have no or low antibody binding or CDC to TKO pig cells) (Figure S2, SDC, http://links.lww.com/TXD/A267 ). 15 …”
Section: Discussionmentioning
confidence: 99%
“…Selecting baboons that have a low or negative CDC to pig cells will be important in mimicking the pig-to-human model (as many humans have no or low antibody binding or CDC to TKO pig cells) (Figure S2, SDC, http://links.lww.com/TXD/A267 ). 15 …”
Section: Discussionmentioning
confidence: 99%
“…Xenotransplantation could provide an unlimited supply of tissue for clinical transplantation, thereby providing the ultimate solution to the shortage of donors 1 . However, the aggressive cell-mediated immune rejection of xenografts is a major obstacle to clinical application 2 and most of the immune suppressive drugs used to extend the survival of xenografts are highly toxic with some not suitable for human use 3 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Because of their strong genetic, anatomical and physiological similarities with humans, mini pigs have advantages over rodent models as pharmacokinetic models. 12 Studies have shown that in many cases, mini pigs are more suitable for toxicology tests than dogs or monkeys. 13…”
Section: Discussionmentioning
confidence: 99%